2001
DOI: 10.1101/gr.196301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Encoding Amino Acid Permeases by Inactivation of Selected ORFs from the Synechocystis Genomic Sequence

Abstract: Genes encoding elements of four amino acid permeases were identified by insertional inactivation of ORFs from the genomic sequence of the cyanobacterium Synechocystis sp. strain PCC 6803 whose putative products are homologous to amino acid permease proteins from other bacteria. A transport system for neutral amino acids and histidine and a transport system for basic amino acids and glutamine were identified as ABC-type transporters, whereas Na + -dependent transport of glutamate was found to be mediated by at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 19 publications
2
72
0
Order By: Relevance
“…6). Addition of Glu did not compensate for the growth defect in the mutant, despite the fact that this cyanobacterium possesses a Glu transporter (Quintero et al, 2001). Pyruvate mitigated the inhibition of growth to some extent.…”
Section: Effects Of Addition Of Metabolites On the Dcyabrb2 Mutant Unmentioning
confidence: 96%
“…6). Addition of Glu did not compensate for the growth defect in the mutant, despite the fact that this cyanobacterium possesses a Glu transporter (Quintero et al, 2001). Pyruvate mitigated the inhibition of growth to some extent.…”
Section: Effects Of Addition Of Metabolites On the Dcyabrb2 Mutant Unmentioning
confidence: 96%
“…PCC 6803 was the only known glutamate transporter in cyanobacteria. 9) We searched for the homologous gene in A. halophytica, and based on shotgun sequencing of A. halophytica, we found that A. halophytica contains a gene (ApgltS) which has low homology to SygltS (slr1145) of Synechocystis sp. PCC 6803.…”
Section: Resultsmentioning
confidence: 99%
“…PCC 6803 is mediated by GltS and Gtr, although the involvement of yet another transporter has been suggested. 9) However, the molecular properties of GltS have not been explored in any cyanobacterium.…”
mentioning
confidence: 99%
See 2 more Smart Citations